Human Resources of Government Apparatus and Public Service Professionalism - Titien Agustina; Nurhikmah Nurhikmah; Fanlia Prima Jaya; Muhammad Nurdin; Alfiannor Alfiannor; Arfie Yasrie; Devi Rusvitawati; Diana Diana (CV. Media Digital Publikasi Indonesia, 2023)
Human resources (HR) are crucial in all facets of life. Institutional responsibilities are part of the effort required to provide public services. This study aimed to assess the public services provided by all local government working units (SKPD), technical implementing units (UPT), and local companies (Perusda) in Banjarmasin. Measuring public services helps determine the public's concern and allows the community to participate in how well human resources of government apparatus do their jobs and responsibilities for all citizens. The study method was a survey of 700 people in the community who have used public services in different categories and fields in 2021. This study showed that the quality and quantity of public services the Banjarmasin municipal government offers have improved. It also showed that public service personnel's (human resources of government apparatus) professionalism has improved and that those served care about the facilities required for public administration to function. This implied how the Banjarmasin municipal government managed public services through the human resources or government apparatus on each SKPD/UPT/Perusda positively impacted the society receiving the service.